Visual Impairment in Orbitofrontal and Sphenoidal Fibrous Dysplasia Associated with Sphenoid Sinus Mucocele - Claudia Florida Costea; Andrei Cucu; Victor Vlad Costan; Gabriela Florența Dumitrescu; Anca Sava; Dana Mihaela Turliuc (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2015)
The orbitofrontal fibrous dysplasia is a rare, non-malignant disease that involves the development and thickening of craniofacial bones, causing facial asymmetry, visual, neurological and dental complications. Decreased visual acuity in orbitofrontal and sphenoidal fibrous dysplasia appears as a result of compressive lesions on the optic nerve. The aim of this article is to present the ophthalmologic complications due to the association of two entities that both involved the optic nerve: orbitofrontal fibrous dysplasia associated with a large sphenoid sinus mucocele. We report the case of a 20-years old male patient, who was admitted to the Neurosurgery Unit II of "Prof. Dr. Nicolae Oblu" Emergency Clinical Hospital, Iassy, Romania, for headache, sudden decrease in visual acuity of both eyes in the last month, though more markedly in his right eye and facial deformity with right frontal bony bulging.The patient hadn't in his previous medical history any dermatological or endocrinological diseases.The ophthalmologic examination revealed that the visual acuity of the right eye was hand movements and best corrected visual acuity of the left eye was 20/60. Conventional X-ray, CT and MRI investigations showed an orbitofrontal and sphenoidal fibrous dysplasia associated with a large sphenoid sinus mucocele,  located in the anterior and middle cranial fossa. Two surgical procedures were performed, the first being an attempt to perform a bilateral decompression of the optic nerve and in the second one, was evacuated the large sphenoid sinus mucocele, that compressed the optic chiasm. The first histopathological  examination confirmed that the orbitofrontal and sphenoidal lesion had a typical appearance of fibrous dysplasia and the second biopsy revealed a sphenoid sinus mucocele. Six months after the evacuation of the sphenoid sinus mucocele, patient recovered completely his vision only in the left eye (20/20) and the right eye had no light perception, he also developed a peripheral right facial nerve palsy.